Postnatal reduction of tuberous sclerosis complex 1 expression in astrocytes and neurons causes seizures in an age‐dependent manner. (12th October 2017) - Zou, Jia; Zhang, Bo; Gutmann, David H.; Wong, Michael
Summary: Objective: Epilepsy is one of the most prominent symptoms of tuberous sclerosis complex (TSC), a genetic disorder, and may be related to developmental defects resulting from impaired TSC1 or TSC2 gene function in astrocytes and neurons. Inactivation of the Tsc1 gene driven by a glial‐fibrillary acidic protein (GFAP) promoter during embryonic brain development leads to widespread pathologic effects on astrocytes and neurons, culminating in severe, progressive epilepsy in mice ( Tsc1 GFAP ‐Cre mice). However, the developmental timing and cellular specificity relevant to epileptogenesis in this model has not been well defined. The present study evaluates the effect of postnatal Tsc1 gene inactivation on pathologic features of astrocytes and neurons and development of epilepsy. Methods: An inducible Tsc1 knock‐out mouse was created utilizing a tamoxifen‐driven GFAP‐CreER line ( Tsc1 GFAP ‐Cre ER mice) with TSC1 reduction induced postnatally at 2 and 6 weeks of age, and compared to conventional Tsc1 GFAP ‐Cre mice with prenatal TSC1 reduction. Western blotting, immunohistochemistry, histology, and video–electroencephalography (EEG) assessed mechanistic target of rapamycin (mTOR) pathway activation, astrogliosis, neuronal organization, and spontaneous seizures, respectively. Results: Tsc1 gene inactivation at 2 weeks of age was sufficient to cause astrogliosis and mild epilepsy in Tsc1 GFAP ‐Cre ER mice, but the phenotype was much less severe than that observed with prenatal Tsc1 gene inactivation in Tsc1 GFAP ‐Cre mice. Both astrocytes and neurons were affected by prenatal and postnatal Tsc1 gene activation to a degree similar to the severity of epilepsy, suggesting that both cellular types may contribute to epileptogenesis. Significance: These findings support a model in which the developmental timing of TSC1 loss dictates the severity of neuronal and glial abnormalities and resulting epilepsy.